Increasing the Quality of Bank Service Systems at the Customer Service Office (CSO) for Sustainability Customer Trust - Zulkarnaen, Iskandar; Apriyani, Apriyani; Nuryono, Arif; Prasmoro, Alloysius Vendhi; Kurnia, Hibarkah (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
In the last six months, one of the Bank Central Asia (BCA) in Central Jakarta received various kinds of complaints from customers every month. The complaint relates to the Customer Service Officer (CSO) who is not optimal in terms of service. This is of concern to research, because competition in the service industry, especially banking, is increasing every year. This research aims to analyze improving the quality of service to customers and provide appropriate solutions for the continued trust of BCA customers. This research method uses the Quality Function Deployment (QFD) method combined with customer complaint data through questionnaires and comparison data with competitor banks through benchmarking. This research found six causes of declining CSO service quality based on Voice of Customer (VOC). Meanwhile, from the 6 causes of problems, seven corrective actions were produced using a correlation matrix and technical actions to improve the quality of CSO services. After measuring aspects using the QFD method, the resulting importance level was 17%, meaning it was important to repair, the aspect difficulty level was 2%, meaning it was easy to repair, and the estimated cost aspect was 15%, meaning the cost was low in repairs. Corrective actions on the part of the CSO have been maximized in providing services to customers at BCA Branch Unit Offices (BUO). Gajah Mada, Central Jakarta.  So that in the coming years the quality of CSO services will continue to be evaluated to reduce complaints from BCA customers.